"Anyone can become a refugee:" strategies for empathic concern in activist documentaries on migration. (November 2020) - Briciu, Bianca
Abstract: This article discusses the narrative and cinematic strategies used by activist documentaries on migration to enhance the empathy of spectators for the experiences of refugees. Empathy is not simply an emotion but an intersubjective skill of accessing the world of others and sensing our human interconnectedness. The paper focuses on Exodus, Our Journey to Europe and Exodus, The Journey Continues, a series of six documentaries, arguing that they create a viewing experience that enhances empathic concern through the use of haptic visuality, narrative witnessing and the personal accounts of the migrant protagonists. This paper examines empathy and its connections with cinematic identification, analyzing how it becomes articulated in activist documentaries through the representation of a multidimensional image of migrants. Highlights: This article discusses the emotional strategy of empathy that documentaries use to engage spectators with the experiences of refugees. Empathy is not simply an emotion but an intersubjective experience of accessing the world of others and sensing our human interconnectedness. The series of documentaries, Exodus, Our Journey to Europe and Exodus, Our Journey Continues, create a viewing experience that enhances cognitive and affective empathy through the use of haptic visuality, narrative witnessing and personal accounts of refugees, inviting spectators to experience empathic concern for the Other. This paper examines the emotion of empathy and its connections with cinematic identification, analyzing how it becomes articulated in refugee documentaries to create a mind changing impact on potential spectators.